2020
DOI: 10.1002/micr.30655
|View full text |Cite
|
Sign up to set email alerts
|

Bone nonunion management in children with a vascularized tibial periosteal graft

Abstract: Background: Vascularized periosteal graft have demonstrated a tremendous bone healing capacity in children. The objective is to report outcomes on the use of vascularized tibial periosteal graft (VTPG) during bone reconstruction in a series of children with complex bone healing problems. Patients and methods: Cases were collected retrospectively since May 2013 to May 2019, excluding cases of congenital pseudarthrosis of the tibia. Mean age at surgery was 12.8 (range 11-18) years. Indications included treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The PMFC flap should be considered as an alternative in cases of Soldado et al, 2020). The same group also reported a favorable outcome in adult scaphoid nonunion management with a similar technique (Barrera-Ochoa et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The PMFC flap should be considered as an alternative in cases of Soldado et al, 2020). The same group also reported a favorable outcome in adult scaphoid nonunion management with a similar technique (Barrera-Ochoa et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have assessed the use of periosteal flaps for nonunion management, mostly in children. Soldado et al have shown excellent results using various free and pedicled periosteal flaps without bone graft in skeletally immature patients (Barrera‐Ochoa et al, 2018 ; Soldado et al, 2020 ). The same group also reported a favorable outcome in adult scaphoid nonunion management with a similar technique (Barrera‐Ochoa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…High union rates and excellent clinical outcomes have been reported with VPF in the treatment of complex situations in the pediatric population, including (such as recalcitrant nonunion, avascular necrosis, or massive bone defects; Soldado et al, 2012; 2015). In our experience, some VPF have been used with good results in these complex situations, including vascularized tibial periosteal graft in children with complex bone healing problems or vascularized humeral periosteal flap to treat lateral humeral condyle nonunion (Barrera‐Ochoa et al, 2019; Soldado et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For VTPG harvesting, we adhered to the technique previously described by Soldado et al (2020). A skin island was included in all cases to monitor vascular anastomosis status.…”
Section: Methodsmentioning
confidence: 99%